The View From Outside: Equality of Member States From the Perspective of National Constitutional Laws and Courts - Zs. Varga, András (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This study focuses on the development of the relationship between national courts and the European Union’s supranational legal institutions as part of the changes in the understanding of the concept of the rule of law. These changes have led to complex relationships between sovereignty, legal authority, and judicial independence. The disintegration of empires after the World Wars and the formation of international institutions have changed the global power balance, and through these changes, the rule of law concept became a cornerstone of modern European legal systems. This development also embraced the increasing prominence of courts. The 20th century required new constitutional frameworks, which were often enforced by independent constitutional courts, and the role of the courts, especially constitutional courts, has changed. They have become crucial in maintaining the balance of power within states, particularly in newly democratised countries. This process has often led to judicial activism coupled with supranational influences, which have led to tensions within the state and between national sovereignty and EU law. This study discusses the challenges posed by the increasing authority of the Court of Justice of the European Union (CJEU) and how the concept of constitutional dialogue has given way to a more hierarchical relationship between the CJEU and national courts. The study further suggests the need for greater cooperation among national, supreme, and constitutional courts.